PENERAPAN PMRI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV B SD NEGERI 102 PEKANBARU - Butet Kumala Sari; Hendri Marhadi; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research was mathematic learning in fourth grade students SDN 102 Pekanbaru still low with average value 48 with minimum completeness criteria (KKM 75).The purpose 0f this research was to improve mathematic learning outcomes 0f the fourth grade (IV) students SDN 102 Pekanbaru with PMRI. This research was classroom action research with two circles. The subject were students of class IV SDN 102 Pekanbaru on 2016/2017 academic years with amounted to 25 students consisting of 13 men and 12 women. Base on analysis result observation paper of teacher and students activity sheet seen rising each meeting, teacher activity at first meeting of first circle was 69% good category and at the second meeting was 75 % with very good category. At the second circle, teachers activity at the first meeting was 81 % and the second meeting was 94 % with very good category. Student activities at first meeting of first circle was 63% good category and at the second meeting was 69 % with very good category. At the second circle, student activity on the first meeting was 78% and at the second meeting was 88% with very good category. Mathematic learning outcomes before implementation cooperatives number head together type learning model average 48, after implementation cooperatives number head together type learning model at UH 1 was 81 and at UH II was 89 that improve about 8 point. Implementation of PMRI can improve learning outcomes of the fourth grade students SDN 102 Pekanbaru. Key Word: Mathematics Realistic Indonesia Approach, Mathematic studies achievment